Tax Based on Double Income Taxpayer Perspective (Jurnal Dinamika Akuntansi, 2019)
This research is a case study approach. This research is a qualitative study using the interpretive paradigm. The data collection technique of this study used interviews with the Miles and Hubberman data analysis techniques. The purpose of this study was to determine the point of view of the fairness of the tax amnesty policy of taxpayers with multiple incomes. Taxpayers with double income in question are employees who own a business as additional income. The informants from this study were employees of Civil Servants (PNS) who also owned businesses and employees of State-Owned Enterprises (BUMN) who also had businesses in addition to their main work. Tax amnesty is one form of complex Government reform. Pros and cons of tax amnesty are increasingly visible from the public response especially for those who feel they are victims of wrong targets. The results of this study show justice from the subjective point of view of obedient and non-compliant Taxpayers, subjective justice from the perspective of PNS and BUMN, and justice based on the objective side.